Ethical Dimensions of Public Health Actions and Policies With Special Focus on COVID-19 - Saleh, Basma M.; Aly, Eman Mohamed; Hafiz, Marwa; Abdel Gawad, Rana M.; El Kheir-Mataria, Wafa Abu; Salama, Mohamed (Frontiers in Public Health, 2021)
During pandemics, the ethicists, public health professionals, and human rights advocates raise a red flag about different public health actions that should, at best, be addressed through integrated, global policies. How to rationalize the healthcare resources and prioritize the cases is not a recent challenge but the serious concern about that is how to achieve this while not increasing the vulnerability of the disadvantaged population. Health Care professionals use different scoring systems as a part of their decision-making so the medical teams and triage committees can allocate resources for predictable health outcomes and prognosis as well as to appropriately triage the patients accordingly. However, the value of existing scoring systems to manage COVID-19 cases is not well-established yet. Part of this problem includes managing non-COVID patients with chronic medical conditions like non-communicable diseases and addressing their medical needs during the pandemic complex context in a way to avoid worsening their conditions and, on the other hand, avoid hindering the establishment of comprehensive standards for dealing with COVID-19. In this article, we discuss this dilemma as well as how preexisting ethical standards were challenged by COVID-19, We also discuss how monitoring the consistent application of ethical standards during the medical trials of new medications, vaccines or unproven medical interventions is also a critical issue. Conclusion: comprehensive, transparent, and culturally acceptable policies and procedures corresponding to pandemics should be developed globally regarding patient triage, efficient rationing of limited healthcare resources based on clearly defined measures while avoiding disproportionate impacts on vulnerable populations and considering health workers at high risk. Moreover, any such policies should consider bioethical measures for unproven or experimental interventions.